2021
DOI: 10.1093/mnras/stab878
|View full text |Cite
|
Sign up to set email alerts
|

On the duration of the embedded phase of star formation

Abstract: Feedback from massive stars plays a key role in molecular cloud evolution. After the onset of star formation, the young stellar population is exposed by photoionization, winds, supernovae, and radiation pressure from massive stars. Recent observations of nearby galaxies have provided the evolutionary timeline between molecular clouds and exposed young stars, but the duration of the embedded phase of massive star formation is still ill-constrained. We measure how long massive stellar populations remain embedded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
92
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 153 publications
37
92
1
Order By: Relevance
“…These findings are in excellent agreement with the results of Lucas et al (2020), who simulate supernovae in star-forming molecular clouds with and without early stellar feedback (in the form of ionisation and stellar winds). In their study, Lucas et al find that early stellar feedback creates pre-SN cavities with systematically The environmental dependencies found here are consistent with the results of Chevance et al (2020c) and Kim et al (2021), who observed no statistically significant radial trends for the derived feedback time-scales within the uncertainties. Indeed, the increase of feedback pressure reported here does not directly imply accelerated feedback time-scales, as the time-scales depend on other environmental properties that set how rapidly the imparted feedback (which is what we measure) disperses the natal GMCs.…”
Section: Supernova Remnants In the Context Of Early Stellar Feedbacksupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in excellent agreement with the results of Lucas et al (2020), who simulate supernovae in star-forming molecular clouds with and without early stellar feedback (in the form of ionisation and stellar winds). In their study, Lucas et al find that early stellar feedback creates pre-SN cavities with systematically The environmental dependencies found here are consistent with the results of Chevance et al (2020c) and Kim et al (2021), who observed no statistically significant radial trends for the derived feedback time-scales within the uncertainties. Indeed, the increase of feedback pressure reported here does not directly imply accelerated feedback time-scales, as the time-scales depend on other environmental properties that set how rapidly the imparted feedback (which is what we measure) disperses the natal GMCs.…”
Section: Supernova Remnants In the Context Of Early Stellar Feedbacksupporting
confidence: 90%
“…This result has been generalised in recent observational studies by Chevance et al (2020a,c), who have quantified feedback time-scales across nine nearby disc galaxies, finding that GMCs are dispersed within 1−5 Myr after the emergence of massive stars from their dust-enshrouded birth places. This analysis has been extended further by Kim et al (2021) to also encompass the dust embedded stages of star formation than those probed by Chevance et al, and both studies conclude that early (pre-SN) stellar feedback (in the form of stellar winds and photoionisation in particular) is a major component driving the GMC disruption. These results are consistent with optical/near-ultraviolet studies of the young cluster population, which find that clusters become unassociated with their natal clouds after just a few Myr (e.g.…”
Section: Supernova Remnants In the Context Of Early Stellar Feedbackmentioning
confidence: 93%
“…of star formation (e.g., Murray 2011;Lee et al 2016;Kruijssen et al 2019), to constrain the feedback mechanisms responsible for cloud destruction (e.g., Chevance et al 2020b), and to assess the fraction of non-star-forming molecular material (e.g., Schinnerer et al 2019;Chevance et al 2020a;Kim et al 2021a).…”
Section: Key Physics At or Near Cloud Scalesmentioning
confidence: 99%
“…Whilst this is true for the majority of cases, there is a known cross-over between the Hα emitting phase and the embedded phase, which typically corresponds to around a third of the total Hα emitting lifetime (e.g. Kim et al 2021a). The effect of the local environment and the initial conditions of the H II regions will be assessed in detail in future work, and here we adopt 𝑃 de for the external dynamical pressure.…”
Section: External (Dynamical) Pressure Componentsmentioning
confidence: 99%